MARKETING TOOLS FOR INTERNATIONAL TOURISM FLOWS BALANCING: EXPERIENCE OF UKRAINE AND POLAND - Iryna Babets; Mariya Fleychuk (Izdevnieciba "Baltija Publishing", 2021)
The article provides a comparative analysis of trends in domestic and foreign tourism in Ukraine and Poland during the COVID-19 pandemic. The main directions and tools of marketing policy of balancing tourist flows for socio-economic development of the researched countries are analyzed. The main subject of the research is marketing tools for balancing international tourist flows in the investigated countries, taking into account the experience of other countries in which the field of tourism is developed. The research methodology provides for the analysis of the dynamics of tourist flows in Poland and Ukraine, the use of methods and tools of fuzzy logic using Mathlab software and the use of a matrix method of analysis to study the development of tourism at the regional level. The study used data from the World Bank, the International Monetary Fund in post-socialist countries, as well as the results of the Global Market Research-2020 and data from statistical agencies of Ukraine and Poland. It is emphasized that formation of an effective marketing policy to balance the flow of international tourism at the local level should be with the participation of the private sector and local governments. The purpose of the article: outline marketing tools for balancing international tourism flows in Ukraine and Poland, especially during the Covid-19 pandemic. Conclusions. In summary, the study identified such generalized tools of modern marketing that are most relevant in the development of policies to balance tourist flows in Ukraine and Poland, as well as in other countries, especially in the pandemic Covid-19: creating content for electronic networks (content), social media marketing (SMM), landing page or standard website, search engine optimization (SEO), media advertising, teaser advertising, consumer product support, e-mails (emails), viral marketing, strategic partnership, CPA-marketing, creation of a marketing channel, application of a comprehensive strategy of smart-tourism.